2019
DOI: 10.1371/journal.pbio.3000026
|View full text |Cite
|
Sign up to set email alerts
|

Chronotopic maps in human supplementary motor area

Abstract: Time is a fundamental dimension of everyday experiences. We can unmistakably sense its passage and adjust our behavior accordingly. Despite its ubiquity, the neuronal mechanisms underlying the capacity to perceive time remains unclear. Here, in two experiments using ultrahigh-field 7-Tesla (7T) functional magnetic resonance imaging (fMRI), we show that in the medial premotor cortex (supplementary motor area [SMA]) of the human brain, neural units tuned to different durations are orderly mapped in contiguous po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 52 publications
10
79
1
3
Order By: Relevance
“…The hypothesis that perceived duration is achieved through leaky integration of stimulus-related and stimulus-unrelated sensory input is particularly relevant to the debate on models for the perception of time in the scale that ranges from tens of milliseconds up to a few seconds. Our results are in line with other work that assumes temporal integration processes behind the encoding of the passage of time (30,31) and are also in accordance with the idea that sensory-specific areas contribute to time perception (3,32). They are harder to reconcile with the amodal central clock theory (1).…”
Section: Integration Of Sensory Drive and Alternative Modelssupporting
confidence: 92%
“…The hypothesis that perceived duration is achieved through leaky integration of stimulus-related and stimulus-unrelated sensory input is particularly relevant to the debate on models for the perception of time in the scale that ranges from tens of milliseconds up to a few seconds. Our results are in line with other work that assumes temporal integration processes behind the encoding of the passage of time (30,31) and are also in accordance with the idea that sensory-specific areas contribute to time perception (3,32). They are harder to reconcile with the amodal central clock theory (1).…”
Section: Integration Of Sensory Drive and Alternative Modelssupporting
confidence: 92%
“…Of note, connectivity of the right temporoparietal junction and the right fronto-polar cortex represents both polarity and intensity of affective states. In line with topographies of narrative comprehension and memory encoding revealed in high-order associative regions (Baldassano et al, 2017), our results also demonstrate a chronotopic (Protopapa et al, 2019) organization of affect, where distinct brain areas preferentially track changes in the emotional experience at different timescales, ranging from a few to several minutes. complexity (24% of the explained variance) represents how much the affective state is associated with cognitive processes (positive scores), rather than being characterized by fast and automatic responses (negative scores); (c) intensity (16% of the explained variance) denotes whether the experience is perceived as highly (high positive scores) or mildly (low positive scores) emotional.…”
Section: Introductionsupporting
confidence: 90%
“…Previous studies on memory and narrative comprehension Baldassano et al, 2017;Chen et al, 2016) demonstrated that the brain splits the experience at multiple timescales following a hierarchy in which sensory regions extract information in short segments, whereas high-order areas preferentially encode longer events. We reveal that the same happens for the processing of affect, with chronotopic maps (Protopapa et al, 2019) representing the temporal dynamics of the emotional experience at specific timescales. As compared to studies on narrative comprehension and memory, our results highlight relatively slow dynamics, approximately between 3 and 11 minutes.…”
Section: Discussionmentioning
confidence: 71%
“…Many animal and human electrophysiology and neuroimaging studies have searched for potential neural regions or putative mechanisms underlying time perception (15,16). This literature finds potential mechanisms in a diverse set of regions including pre-/supplementary motor areas (11,14,17), parietal areas (18,19), insula (20), midbrain dopaminergic neurons (21), and hippocampus and entorhinal cortex (22)(23)(24)(25). The diversity of neural regions apparently associated with human time perception supports the intuition underlying the population clock approach -that the dynamics of a neural system can be interpreted as reflecting time to an external observer because it is dynamic, i.e.…”
Section: Introductionmentioning
confidence: 99%